The Efficiency of Distance Education Considering the Spread of COVID-19 in Saudi Universities - ALSAYSI, Areej (Journal of Research in Educational Sciences; Vol 13 No 15 (2022): JRES, Volume XIII, Issue 15, Winter 2022DO - 10.14505/jres.v13.15.03, 2022)
The study aimed to verify the efficiency of distance education in light of the spread of COVID-19 in Saudi universities from the students’ point of view. The study reviewed the elements of the effectiveness of distance learning through the verification of the elements of the efficiency of distance education. It used descriptive curricula based on a questionnaire of 29 items distributed over six axes and applied to a random sample of 380 Saudi university students. The key results of the study were as follows. The efficiency of distance education in light of the spread of COVID-19 in Saudi universities was achieved with a degree ranging from medium to very high from the students’ point of view, as the necessary elements for distance education were achieved. In addition, the part of policies, regulations, and ethics in the field of distance education was completed to a high degree, reaching an average of 4.006. Providing the appropriate technology to accomplish the tasks required was achieved to a high degree as well with an average of 3.846. The study recommended that Saudi universities provide training programs to clarify the policies, regulations, and ethics of distance education through electronic education platforms and the Deanship of University Development.